The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3389/fgene.2022.823716
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of a Novel Combined Nomogram for Predicting the Risk of Progression Related to Castration Resistance in Patients With Prostate Cancer

Abstract: Background: The emergence of castration resistance is fatal for patients with prostate cancer (PCa); however, there is still a lack of effective means to detect the early progression. In this study, a novel combined nomogram was established to predict the risk of progression related to castration resistance.Methods: The castration-resistant prostate cancer (CRPC)-related differentially expressed genes (DEGs) were identified by R packages “limma” and “WGCNA” in GSE35988-GPL6480 and GSE70768-GPL10558, respective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 45 publications
3
5
0
Order By: Relevance
“…BCAS1 has been found to be highly expressed in breast cancer cell lines 28 . Consistent with our results, Shuqiang Li reported that it can serve as a biomarker to predict castration‐resistant PCa 29 . RBM47 has been shown to inhibit the progression of several malignancies, including thyroid carcinoma, nasopharyngeal carcinoma, lung cancer and colorectal cancer, whereas its role in PCa has not been characterized 30–33 .…”
Section: Discussionsupporting
confidence: 83%
“…BCAS1 has been found to be highly expressed in breast cancer cell lines 28 . Consistent with our results, Shuqiang Li reported that it can serve as a biomarker to predict castration‐resistant PCa 29 . RBM47 has been shown to inhibit the progression of several malignancies, including thyroid carcinoma, nasopharyngeal carcinoma, lung cancer and colorectal cancer, whereas its role in PCa has not been characterized 30–33 .…”
Section: Discussionsupporting
confidence: 83%
“…In this study, a novel nomogram was established for predicting the probability of specific progression times to CRPC, by integrating five proteins (ARHGEF1, UTP23, ANAPC4, DPT, and CMAS) and two clinical features (tPSA and GS), based on their expression levels and regression coefficients, as demonstrated by the multivariate Cox regression analysis. As a comprehensive scoring system, of which prediction ability was comfirmed by the overall C-index and the AUC values, our results suggest a better discrimination capability than previously published transcriptomic signatures consisting of two to 22 genes 22-25 .…”
Section: Discussionsupporting
confidence: 61%
“…Besides, we compared our risk model with other signatures. Li et al [18] constructed a 2-gene signature PFI prediction model. We determined the risk scores of all samples and performed the ROC and DCA based on their risk score (Fig.…”
Section: Establishment and Validation Of The Risk Modelmentioning
confidence: 99%